2021
DOI: 10.1007/s40815-021-01131-9
|View full text |Cite
|
Sign up to set email alerts
|

Ranking Tourist Attractions through Online Reviews: A Novel Method with Intuitionistic and Hesitant Fuzzy Information Based on Sentiment Analysis

Abstract: Online tourist reviews are the real feeling of tourists after the journey, which have a strong reference value for potential tourists to make travel decisions. However, it is almost impossible for a potential tourist to look through the massive online reviews related to tourist attractions (TAs) so that he/she can make the most appropriate decision. To this end, this paper proposes a recommender system to rank the alternative TAs through online reviews based on aspect-level sentiment analysis and multi-criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 78 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…In particular, only articles published from 2018 to 2020 in Q1/Q2 level (https://www. scimagojr.com/journalrank.php) journals are in Table 1 (Qin et al, 2022). Concerning previous literature, we found that in the education area concentrated on detecting the methodologies and resources used in SA and identifying the main grants of using SA on education data.…”
Section: Related Workmentioning
confidence: 82%
See 1 more Smart Citation
“…In particular, only articles published from 2018 to 2020 in Q1/Q2 level (https://www. scimagojr.com/journalrank.php) journals are in Table 1 (Qin et al, 2022). Concerning previous literature, we found that in the education area concentrated on detecting the methodologies and resources used in SA and identifying the main grants of using SA on education data.…”
Section: Related Workmentioning
confidence: 82%
“…One endeavor in Sentiment analysis is to manage these sources and accordingly separate these evaluations into different classes like positive appraisal or negative evaluation. Another task is to determine whether a given text is enthusiastic, presenting the writer's perspectives, or objective, conveying essentially real factors (Qin, Wang, & Xu, 2022). These tasks were performed at different levels of examination ranging from the document level to the sentence and articulation level (Shao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Also, technically star rating is not accurate and does not represent a true representation of a mobile app as the user may not be satisfied with an app and still award four stars to the app [ 6 ]. Recently, a lot of research has been done to tackle the problem of review anomalies to rank the online reviews based on the sentimental analysis [ 39 , 50 ]. Existing approaches to sentiment analysis using app reviews lack in several aspects.…”
Section: Introductionmentioning
confidence: 99%
“…People's life is inseparable from the support of decision-making [8][9][10], and customer satisfaction is affected by the utility of decision-making. Customer satisfaction with products is driven by big data decision-making, including applications such as perceived satisfaction [11][12] and sentiment analysis [13][14][15][16][17]. However, for the big data of online reviews, will thousands of reviews cause data analysis results to be biased?…”
Section: Introductionmentioning
confidence: 99%